Comparison of blood pressure reduction between treatments of steeping red ginger rhizome (Zingiber officinale R.) and steeping binahong leaves (Anredera cordifolia (Ten.) Steenis) in healthy people with hypertension risk - Djelang Zainuddin Fickri; Arista Wahyu Ningsih; Martina Kurnia Rohmah; Khurin In Wahyuni; Novita E. Winarni; Pahri (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2021)
The potency of red ginger rhizome (Zingiber officinale R.) and binahong leaves (Anredera cordifolia (Ten.) Steenis) has been known to have an antihypertensive effect and can be used in herbal medicine. This study compared the impact of steeping red ginger rhizome and steeping binahong leaves on blood pressure reduction in healthy people with hypertension risk. The research design is a Comparative Quasy Experiment to measure pre-test and post-test blood pressure on treating 3 gr/200 ml steeping the red ginger rhizome (S1) and 3 gr/200 ml steeping binahong leaves (S2). The number of respondents was 64 according to the inclusion criteria and had obtained ethical clearance. The data were processed statistically. The experiment showed that the S1 group had a significant difference in systolic blood pressure reduction compared with the control treatments, but there was no significant difference in diastolic blood pressure reduction compared with controls. Meanwhile, in the S2 group, there was a significant difference in systolic blood pressure reduction compared with the control treatments, but there was no significant difference in diastolic blood pressure reduction compared with controls. Between the treatment of S1 and S2, there was no significant difference in systolic blood pressure reduction, which means that both red ginger and binahong seed had the same effect on systolic blood pressure. Treatment of steeping red ginger rhizome and steeping binahong leaves has a similar effect on systolic blood pressure reduction.